Penentuan Nilai Diagnostic Reference Level (DRL) pada Pasien Abdomen menggunakan CT-Scan 128 di Instalasi RSUD A.W. Sjahranie Samarinda - Jannah, Raudatul; Munir, Rahmawati; Putri, Erlinda Ratnasari (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2023)
Diagnostic Reference Level (DRL) is a form of investigative level used as a tool to help optimize protection in radiation exposure for diagnostic and interventional procedures. In simple terms, DRL is the amount of dose that is set and becomes a reference in identifying the reception of high radiation doses received by patients for certain types of examinations. DRL aims to optimize the use of radiation in medicine and help avoid overexposure to radiation. The purpose of this study was to determine the local DRL value on the examination of the abdomen at the Radiology Installation of A.W. Sjahranie Hospital Samarinda. Data processing in this study was carried out with quantitative analysis techniques, namely descriptive statistics. This analysis technique used secondary data obtained from the results of recaptures or archival books for examination of the abdomen. Data processing was carried out with a measure of diversity through the calculation of the third quartile (Q3) in the data distribution. It was assumed that 75% of patients performed examinations with a common diagnosis. The results of these calculations are visualized in the form of a graph of the relationship of CTDIvol with the number of patients and a graph of the relationship of DLP with the number of patients. In the abdomen examination, a CTDIvol value of 12 mGy and a DLP value of 1545.5 mGy.cm. The conclusion obtained from this study is the DRL value at A.W. Sjahranie Hospital Samarinda is relatively low, but it still needs to be optimized by medical physicists.